Experimental and Numerical Study on Roll Damping Structure of Floating Crane Catamaran in Free Floating and Moored Conditions - Eko Budi Djatmiko; Murdjito Murdjito; Muhamad Fadkhurrohman Aziz; Baharuddin Ali (International Journal of Offshore and Coastal Engineering, 2020)
This research discusses the experimental study of free decay test This research discusses related to the experimental study of free decay test motion roll on the catamaran floating crane structure which is reviewed from free-floating and moored conditions. Experiments were conducted on the facilities of Maneuvering and Ocean Engineering Basin owned by the BTH – BPPT. The structure used as an experiment was a model of the catamaran floating crane with a scale of 1:36. The test is carried out with a horizontal mooring link system Taken from mooring system modelling, spring stiffness is used as a reference for mooring rope stiffness in numerical analysis. The analysis carried out in this final project is to compare the experimental results of the decay test with the results of the analysis using Moses software. From the results of the experiments obtained a comparison of free-floating conditions to tethered to decay tests of 38%, 8%, and 9% for linear damping values, then 93%, 12%, and 13% for quadratic damping values. Comparison of experiment results to numerical results found a difference of 128.39% for decay test 1 for quadratic damping value, then in decay test 2 and decay test 3 against the numerical got difference of 60.80% and 66.83% in linear damping value.